The makerspace experience and teacher professional development. Issue 2 (15th March 2017) - Paganelli, Andrea; Cribbs, Jennifer D.; 'Silvie' Huang, Xiaoxia; Pereira, Nielsen; Huss, Jeanine; Chandler, Wanda; Paganelli, Anthony
Abstract : This study explored the use of makerspaces as a professional development activity when examined through the analysis of qualitative data reflecting participant experience. The data were gathered in the course of a professional development opportunity at a university during a conference held on campus. The researchers wanted to select an innovative form of professional development for implementation within a traditional conference format. Both to match innovation and to accommodate a traditional time frame (one hour), the concept of makerspace was chosen. Multiple makerspace sessions were developed as professional development opportunities. The participant, practicing teachers would be experiencing the makerspace as if they were students. The research team wanted to explore the experiences and perceptions of the participants from multiple perspectives, including those who participated as learners and those who participated as facilitators, or leaders as termed in this article. A phenomenological approach was used to analyze data collected from three instruments: participant survey; leader reflection; and observer protocol. The data collected allowed researchers to observe a makerspace experience from multiple perspectives, thereby providing insight into the use of makerspaces as professional development and within the educational setting as a whole.